The effect of zirconium tungstate (ZT) particles on the structure and tribological behavior of polyetherimide/polytetrafluoroethylene matrix composites - He C. J.; Buslovich D. G. Dmitry Gennadjevich; Tarasov S. Yu. Sergei Yulievich; Panin S. V. Sergey Viktorovich (2024, 2024)
Текстовый файл